2019
DOI: 10.4049/jimmunol.1801645
|View full text |Cite
|
Sign up to set email alerts
|

FTRCA1, a Species-Specific Member of finTRIM Family, Negatively Regulates Fish IFN Response through Autophage-Lysosomal Degradation of TBK1

Abstract: In mammals, tripartite motif (TRIM) proteins have emerged as pivotal players endowed with, directly, antiviral effects and, indirectly, modulatory capacity of the innate immune response. An unprecedented expansion of TRIM family has occurred in fish; however, the functional role of fish TRIM family members remains largely unknown. In this study, we identify a species-specific TRIM gene from crucian carp Carassius auratus, named FTRCA1, phylogenetically similar to the members of finTRIM, a subfamily of TRIM exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…First, grass carp SARM1 inhibited GCRV-triggered IFN-I response by affecting the expressions of TRIF, MyD88, IPS-1, TRAF6, TBK1, IRF3, and IRF7 in TRIF-, MyD88-, and IPS-1-dependent pathways ( 29 ). In addition, zebrafish STAT6, FGFR3, MVP, NDRG1a, RPZ5, and FTRCA1 suppressed IFN production by attenuating the kinase activity of TBK1 ( 30 , 31 ), degrading TBK1 ( 32 , 33 ) and phosphorylated IRF7 ( 34 , 35 ), or attenuating IRF7 transcription ( 36 ). Using the luciferase reporter assay system, our previous study ( 18 ) and the present study revealed that TBK1 isoforms, TBK1_tv1–TBK1_tv3, had the same function in inhibiting RLR-mediated type I IFN production with or without SVCV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, grass carp SARM1 inhibited GCRV-triggered IFN-I response by affecting the expressions of TRIF, MyD88, IPS-1, TRAF6, TBK1, IRF3, and IRF7 in TRIF-, MyD88-, and IPS-1-dependent pathways ( 29 ). In addition, zebrafish STAT6, FGFR3, MVP, NDRG1a, RPZ5, and FTRCA1 suppressed IFN production by attenuating the kinase activity of TBK1 ( 30 , 31 ), degrading TBK1 ( 32 , 33 ) and phosphorylated IRF7 ( 34 , 35 ), or attenuating IRF7 transcription ( 36 ). Using the luciferase reporter assay system, our previous study ( 18 ) and the present study revealed that TBK1 isoforms, TBK1_tv1–TBK1_tv3, had the same function in inhibiting RLR-mediated type I IFN production with or without SVCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, several deubiquitinases such as CYLD disrupt K63-linked polyubiquitination to terminate TBK1-mediated signaling transduction ( 41 ). Recently, zebrafish MVP and FTRCA1 were found to mediate the lysosome-dependent degradation of TBK1 ( 32 , 33 ). Here, we show that zebrafish TBK1_tv3 is a key kinase that mediates K48-linked ubiquitination at Lys251, Lys256, and Lys271 of TBK1 and promotes TBK1 proteasomal degradation, thus functioning as a negative regulator of type I IFN production.…”
Section: Discussionmentioning
confidence: 99%
“…In the survivors from the resistant strain, the higher PI3K also suggests higher autophagy, since the PI3K/AKT/mTOR pathway enhances this process [28]. Fish TRIM may inhibit the activation of IFN and attenuate IFN regulatory factor (IRF) (41,42). In addition, in carp, nuclear factor, interleukin 3 regulated (NFIL3) stimulated both proinflammatory (e.g., NF-kappa B [NF-κB]) and anti-inflammatory factors (e.g., IL10) (43).…”
Section: Discussionmentioning
confidence: 99%
“…CAB cells were seeded overnight in 6-well plates and transfected with Cg Cxcr4s-pCS2+ and Cg Cxcl12s-pCS2+ respectively using FuGENE HD Transfection Reagent (Promega, Madison, USA) ( 40 , 43 ). After 24 h transfection, 1 μg/ml polyinosinic:polycytidylic acid (poly(I:C)), was transfected to induce the expression of immune genes ( 44 , 45 ). The cells were collected in TRIzol reagent (Invitrogen, Carlsbad, USA) after 24 h stimulation.…”
Section: Methodsmentioning
confidence: 99%